2009
DOI: 10.1029/2009jb006338
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh‐resolution seismic reflection imaging of the Alpine Fault, New Zealand

Abstract: [1] High-resolution seismic reflection surveys across active fault zones are capable of supplying key structural information required for assessments of seismic hazard and risk.We have recorded a 360 m long ultrahigh-resolution seismic reflection profile across the Alpine Fault in New Zealand. The Alpine Fault, a continental transform that juxtaposes major tectonic plates, is capable of generating large (M > 7.8) damaging earthquakes. Our seismic profile across a northern section of the fault targets fault zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…On this figure, the southwestward continuation of fault strands s1 and s3 and the region of transpressive folding into the area of dense beech forest are inferred. The subsidiary fault strand s2 has also been imaged on an ultra-highresolution reflection seismic profile that was acquired along a line approximately coincident with GPR profile C-C′ (Kaiser et al, 2009;Figs. 2a and 8b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On this figure, the southwestward continuation of fault strands s1 and s3 and the region of transpressive folding into the area of dense beech forest are inferred. The subsidiary fault strand s2 has also been imaged on an ultra-highresolution reflection seismic profile that was acquired along a line approximately coincident with GPR profile C-C′ (Kaiser et al, 2009;Figs. 2a and 8b).…”
Section: Discussionmentioning
confidence: 99%
“…1a and 2b) imaged a steeply dipping fault plane (~80°) in the near surface (<15 m) and revealed evidence for off-fault folding and tilting within a broad~50-m-wide zone of deformation (McClymont et al, 2008a). From interpretations of a recently acquired ultra-high-resolution reflection seismic profile over the same area, Kaiser et al (2009) have demonstrated that the fault dips at 75-80°to the southeast and offsets vertically the dipping surface of underlying Triassic and Paleozoic basement units by~35 m.…”
Section: Introductionmentioning
confidence: 96%
“…The geophysical data used in this study span a range from relatively deep-penetration P-wave seismic reflection to horizontally-polarized shear-wave (SH) seismic reflection to 200-MHz ground penetrating radar with resolution on the order of 10 cm. Thus, geophysical data have been acquired over a range of resolutions to better connect surface geology to deeper features (Bruno et al, 2010a,b;Kaiser et al, 2009;McBride et al, 2010b). In order to characterize the range of structural styles in the Sevier Desert basin, we chose three study sites, the Clear Lake fault scarp, Tabernacle Hill, and Devils Kitchen (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The pattern of faulting at Inchbonnie (i.e., positive flower structures and small step over zones) is unlike the arrangement of alternating strike‐slip and reverse faults observed along the Alpine Fault southwest of our study site [ Norris and Cooper , 1995; Cox and Sutherland , 2007]. By comparison, left‐stepping overlapping fault strands are seen in GPR and high‐resolution seismic reflection data acquired across the Alpine Fault at Calf Paddock to the northeast [ Kaiser et al , 2009; McClymont et al , 2010; Kaiser et al, unpublished manuscript, 2011]. However, fault strands within and outside of the step over zones at Inchbonnie are more numerous and complex than those to the northeast.…”
Section: Discussionmentioning
confidence: 97%
“…However, fault strands within and outside of the step over zones at Inchbonnie are more numerous and complex than those to the northeast. A noticeable difference between the Inchbonnie and Calf Paddock sites is the thickness of sediments ruptured by the Alpine Fault; ∼200 m at the former (based on preliminary processing of high‐resolution seismic reflection data) versus ∼60 m at the latter [ Kaiser et al , 2009, 2011]. It is possible that the sedimentary cover at Calf Paddock is not thick enough to allow the formation of distinct flower structures and multiple fault strands within the step over zones.…”
Section: Discussionmentioning
confidence: 99%